Relationship between gingival recessions and orthodontic treatment – review of literature - Ciok, Edyta; Górski, Bartłomiej; Dylewski, Łukasz; Sobieska, Ewa; Zadurska, Małgorzata (Journal of Stomatology, 2015)
Gingival recessions are anomalies caused by an apical displacement of the gingival margin in relation to the cemento-enamel junction (CEJ) with the exposure of the root surface (buccal prevalence). Orthodontic treatment is known as one of the factors contributing to gingival recessions. There are different mechanisms of the development of gingival recession during orthodontic treatment. The aim of this article was to review literature concerning the impact of orthodontic treatment on the occurrence of gingival recession. An analysis of scientific reports was carried out to examine the relationship between orthodontic treatment and the occurrence of gingival recession at the maxillary and mandibular teeth, as well as between proclination and retroclination of incisors and gingival recessions at these teeth. Based on research to date, it is difficult to define clearly the impact of orthodontic treatment on the periodontal status. Currently there is a lack of prospective clinical trials which may help orthodontists in planning and conducting treatment of patients.